The Influence of HRM Practices on Organizational Performance Through Innovation as a Mediating Variable in Government Institutions - Silvinho Manuel; Setia Tjahyanti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The aim of this study is to understand the effect of HRM Practice which consists of Selective Recruitment, Training, Participation in Decision Making, and Rewarding on Organizational Business Performance with Innovation as a mediating variable in several government institutions in Jakarta, especially ASN employees. The object of this research is several government institutions in Jakarta with descriptive and causality research forms. The sample in this study were ASN employees with echelon 3 & 4 levels of position as many as 139 employees. This study uses non probability sampling technique with purposive sampling method. The data collection technique used a questionnaire method. This study uses the SEM-PLS technique to process data. The results of this study indicate that Selective Recruitment has no influence on Innovation, while Training, Participation in Decision Making and Rewarding have an influence on Innovation, besides that Innovation, Training, and Rewarding have an influence on Organizational Business Performance, while Selective Recruitment and Participation in Decision Making have no influence on Organizational Business Performance, and Innovation has a mediating effect between the influence of Participation in Decision Making, and Rewarding variables on Organizational Business Performance, but Innovation does not have a mediating effect between the influence of Selective Recruitment and Training variables on Organizational Business Performance.